Effect of substitution of Sn for Bi on structural and electrical transport properties of SnS thin films (2010)
In this work, results are reported concerning the effect of the Bi concentration on the structural and electrical transport properties of SnS thin films, grown through a chemical reaction of the metallic precursors with elemental sulfur (sulfurization) in a two-stage process. XRD measurements revealed that the samples deposited by sulfurization of Sn or Bi grow in the SnS and Bi2S3 phases, respectively, whereas those obtained by sulfurization of a Sn:Bi alloy grow with a mixture of several phases. Special emphasis was placed on studying through ? versus T measurements, the effect of the Bi concentration on the transport properties of SnS:Bi films. To identify the dominant transport mechanisms, the ? versus T curves were analyzed in two different temperature ranges. It was also found that in the range of temperatures greater than 300 K, the conductivity is predominantly affected by transport of free carriers in extended states of the conduction band, whereas in the range of temperatures below 250 K, the conductivity is dominated by the VRH (variable range hopping) transport mechanism.